Consumers preference toward broadband service / Suhaimi Ahmad - Ahmad, Suhaimi (2010)
This research has been done as a partial fulfillment of the requirement for the Business Management Faculty in order to graduate. The purpose of this paper is to identify the customers' preference toward broadband service at Kota Kinabalu. A questionnaire was designed and answered by customer at Kota Kinabalu also though online survey. Convenience sample was used for this research. Based on the research finding, the customers at Kota Kinabalu area can divided into five group of segment such as student, private sector worker, public sector worker, entrepreneur and self-employment. From the finding most of the customer of using broadband come from student. This group of segment aware using broadband but very sensitive for the price of broadband because there don't have own money to pay the broadband service other segment is not sensitive on price of broadband because their have on money to pay the broadband service. Further more, the finding also identify the factor can influence costumer to using broadband such as price, coverage, lifestyle and speed. Based on the finding also the researcher identify the demographic of the respondent can influence to using broadband such as income and Occupation. There a few recommendation for this study where it can be use for future researcher.